A double e-shape microstripe antenna design with proximity coupling techniques - Lukman Medriavin Silalahi; Imelda Uli Vistalina Simanjuntak; Agus Dendi Rochendi (JURNAL INFOTEL, 2021)
Wireless technology is currently growing along with the increasing need for communication in society. This of course must be supported by better and more efficient device specifications, one of which is the antenna. Microstrip antenna is currently one type of antenna that is widely carried out by lecturers and students because of its shape that can be arranged in such a way that it is expected to be more efficient and practical. In this research, a Double E-shaped microstrip antenna with proximity coupling technique will be designed which will be applied in S-Band services. The S-Band service itself is in the 2-4 GHz frequency range which can serve broadband services. The initial stage of the design takes into account the dimensions of the antenna using the applicable formula to obtain suitable dimensions, then optimization of the feed slot and position of the letter E on the antenna patch uses Ansoft HFSS simulation to obtain the best optimization results. From the design results, it is expected to obtain a microstrip antenna in the form of Double E-shaped with Proximity Coupling technique with a working frequency of 2.5 GHz, a return loss of -18.573 dB, a bandwidth of 144 MHz, a VSWR of 1.265 and a gain of 5.8 dB with the results of the omnidirectional radiation pattern being met as expected.